PENGARUH KEINGINAN MENIRU DAN FOMO DALAM PRODUK KOSMETIK YANG DIENDORSE OLEH SOSIAL MEDIA INFLUENCER - Uswatun Hasanah; Asep Hermawan (STMIK Widuri Jakarta, 2024)
This research aims to analyze the influence of Imitation of Influencer, Social Comparison, Materialism, and Fear of Missing Out (FOMO) on Buying Intention. Data were collected through questionnaires from consumers who follow the social media accounts of three beauty influencers, namely Tasya Farasya, Nanda Arsyinta, and Hanum Mega, and are domiciled in Jakarta. The study used a sample size of 220 respondents with purposive sampling technique. The data analysis method employed in this research is Structural Equation Model (SEM) using AMOS 21 software. The results indicate that Imitation of Influencer has a positive influence on Social Comparison, Imitation of Influencer does not have a positive influence on Materialism, Social Comparison has a positive influence on FOMO, FOMO has a positive influence on Buying Intention, and Materialism has a positive influence on Buying Intention.